Performance Of Vaname Shrimp (Litopenaeus Vannamei) Cultured On Green Water And Brown Water Biofloc Systems - Supono Supono; Mega Cania; Zevinna Kurnia W; Agus Setyawan; Deny Sapto C.U (Barakuda'45, 2022)
Vannamei shrimp (Litopenaeus vannamei) is one of the mainstay commodities that can increase the country's foreign exchange because it has a fairly high selling value in the global market. Several problems in aquaculture can reduce vaname shrimp production such as disease, water quality degradation, and high feed conversion values. Biofloc is an alternative technology that can be applied to overcome the problems in shrimp farming. There are two types of biofloc technology, namely green water biofloc and brown water biofloc. This study aimed to study the effect of the application of the two biofloc systems on growth, survival rate, and feed conversion ratio of vaname shrimp. This study used a completely randomized design consisting of 3 treatments with 3 replications. The treatments were: (A) control, (B) green water biofloc, and (C) brown water biofloc. Shrimp rearing was carried out for 30 days, using a container with a volume of 70 liters of water. Each treatment unit was filled with 70 PL 10 fry, equivalent to 1 PL/liter. The results showed that the type of biofloc system affected the growth and feed conversion ratio of vaname shrimp, but had no effect on the survival rate of vaname shrimp. Green water biofloc produces better growth and feed conversion than brown water biofloc and control